2017
DOI: 10.1111/apt.14048
|View full text |Cite
|
Sign up to set email alerts
|

Performing routine follow‐up biopsy 1 year after diagnosis does not affect long‐term outcomes in coeliac disease

Abstract: Severe disease at diagnosis predicted the record of a repeat biopsy and incomplete mucosal recovery. Neither lacking biopsy nor incomplete recovery in a relative short time span of 1 year was associated with poorer long-term outcome, although survival bias cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 42 publications
0
54
2
1
Order By: Relevance
“…We found the prevalence of regular follow-up to be only 15% in Finnish coeliac disease patients (16). This is in stark contrast to our national guidelines that recommend regular long-term clinical and serological follow-up in all patients (Collin 2010).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We found the prevalence of regular follow-up to be only 15% in Finnish coeliac disease patients (16). This is in stark contrast to our national guidelines that recommend regular long-term clinical and serological follow-up in all patients (Collin 2010).…”
Section: Discussioncontrasting
confidence: 77%
“…However, there is a paucity of evidence as to how the follow-up is actually implemented in clinical practice, and whether the absence of follow-up really affects the long-term coping and health of the patients (9)(10)(11)(12)(13)(14)(15). Interestingly, in a 15-year follow-up we recently found that the lack of a repeat biopsy one year after coeliac disease diagnosis is not associated with an increased risk of adverse outcomes such as reduced well-being or malignancies (16). This would indicate that the association between the presence of follow-up and the prognosis of coeliac disease is more complex than one might expect.…”
Section: Introductionmentioning
confidence: 99%
“…In this excellent paper by Pekki et al., the Finns have once again given us a contribution which provides answers to uncertainties in the management of patients with coeliac disease . In this large clinical study (n=760), they have demonstrated that at 1 year 42% have persisting histological abnormalities (repeat biopsy was available in n=476).…”
mentioning
confidence: 97%
“…The adherence to GFD leads to healing of mucosal damage and disappearance of Ab against tTG, endomysium and gliadins (Catassi and Fasano 2010, Husby et al 2012, Nevoral et al 2014, Björck et al 2015, Balakireva and Zamyatnin 2016, Wolf et al 2017. Although a longlasting and incomplete histological recovery, persistence of symptoms and discrepancy in serum levels of Ab against tTG and deamidated gliadin in CLD patients on a GFD may occur, the histological analysis of smallintestinal mucosa is not usually performed in a follow-up of these patients (Wahab et al 2002, Tursi et al 2003, Osman et al 2014, Pekki et al 2017, Burger et al 2017. However, gliadins and related cereal proteins are not unique foodstuff targets of CLD patients´ immune system.…”
Section: Introductionmentioning
confidence: 99%